The Effect of Moulage on Immersion, Realism, and Learning in a Traffic Accident Training Scenario for Police, Rescue Service, and Ambulance Students. Issue Volume 34:Issue s1(2019) (May 2019) - Prytz, Erik; Jacobsson, Ann; Jonson, Carl-Oscar
Abstract : Introduction: Moulage is the art of creating faked injuries on actors for training purposes. Moulage is commonly used in disaster and emergency medicine training, as it is believed to improve learning through enhanced realism. Aim: The aim of the current study was to test the effect of moulage on perceived realism and learning during a joint exercise featuring students from the police, rescue service, and ambulance service. Methods: The scenario was a car accident with two victims. Students (n = 135) were divided into 12 groups. Moulage was applied to the victim actors for half the groups (n = 67), whereas the other half (n = 68) experienced the scenario without moulage. Victim cards were used in both scenarios. Immersion, realism, and learning was measured on a 100-point scale immediately post-scenario using a questionnaire. Results: Two (moulage group) by three (student population and police, rescue service, or ambulance) ANOVAS on realism, immersion, and learning found no effects on realism or immersion (all p>0.10). There was an effect of student group on learning, F(2, 92) = 3.518, p = 0.034, partial eta square = 0.071, such that the rescue service students had overall lower scores on learning (M = 53.87, SD = 28.29) compared to the police (M = 66.07, SD = 27.55) and ambulance students (M = 74.99, SD = 24.51). Cohen's ds for moulage effect was calculated to 0.144 for immersion, 0.112 for realism, and 0.003 for learning. Discussion: The current study did not find any effects of moulage on immersion, realism, or learning. The effect sizes indicate that any effect of moulage on realism and immersion, should it exist, is in the approximate size of 2-3 points on a 100-point scale. The lack of effect may be due to limitations in the study design, but may also indicate that the use of moulage in addition to victim cards is not necessarily beneficial for novice students' learning.